INGENS - Income Generation through Energy and Complementary Services : Status Report - World Bank (Washington, DC, 2013)
This is an internal status report to ESMAP and Gesellschaft fur Technische Zusammenarbeit (GTZ) which summarizes their ongoing work under a joint energy study entitled INGENS - Income Generation through Energy and. Complementary Services. INGENS has proposed (and started to test) a pragmatic, low-cost approach to improve impact evaluation for future electrification programs: a simple Add-on Electricity Impact Evaluation Instrument (AddIE) for the specific case of firm level productivity which shall be applicable to a broad range of electrification programs (EP), and cost well under US$100k per EP. This tool allows EP managers to move from simple monitoring and reporting of numerical targets achieved to evaluation of the (pro-poor) impact achieved among an important segment of the target group. Five countries were studied: Benin, Ghana, Nigeria, Uganda, and South Africa. This report discusses the overall results of the studies and lessons learned. Finally, it presents next steps and a funding request. There are five annexes at the end of the report, including the questionnaire used, case examples, pictures, and the budget for future funding.